Unique apicomplexan IMC sub-compartment proteins are early markers for apical polarity in the malaria parasite - Poulin,B; Patzewitz,E-M; Brady,D; Silvie,O; Wright,MH; Ferguson,DJP; Wall,RJ; Whipple,S; Guttery,DS; Tate,EW; Wickstead,B; Holder,AA; et al. (Biology Open, 2013)
The phylum Apicomplexa comprises over 5000 intracellularprotozoan parasites, including Plasmodium and Toxoplasma,that are clinically important pathogens affecting humans andlivestock. Malaria parasites belonging to the genusPlasmodium possess a pellicle comprised of a plasmalemmaand inner membrane complex (IMC), which is implicated inparasite motility and invasion. Using live cell imaging andreverse genetics in the rodent malaria model P. berghei, welocalise two unique IMC sub-compartment proteins (ISPs)and examine their role in defining apical polarity duringzygote (ookinete) development. We show that these proteinslocalise to the anterior apical end of the parasite where IMCorganisation is initiated, and are expressed at alldevelopmental stages, especially those that are invasive.Both ISP proteins are N-myristoylated, phosphorylated andmembrane-bound. Gene disruption studies suggest that ISP1is likely essential for parasite development, whereas ISP3 isnot. However, an absence of ISP3 alters the apical localisationof ISP1 in all invasive stages including ookinetes andsporozoites, suggesting a coordinated function for theseproteins in the organisation of apical polarity in the parasite.